2015
DOI: 10.4028/www.scientific.net/amm.773-774.570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nozzle Diameter on the Spray Characteristics of Premix Injector in Burner System

Abstract: Abstract. An essential component of the injector nozzle geometry is to see the results spray atomization and mixture formation of the fuel-air combustion to improve performance, and reduce pollution from a burner. Studies involving the injectors in the combustion burner are still in a small proportion, particularly in the premix injector type. Thus, this study involves the efforts to determine the appropriate diameter of the premix injector where the injector sprays characteristics is produced by using Computa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Premix injectors are a sort of indirect injection in which the fuel is pumped into a sub-chamber to be swirled with compressed air before being sprayed into the combustion chamber area [1]. Many studies have suggested factors that influence the combustion and emissions of the burner.…”
Section: Introductionmentioning
confidence: 99%
“…Premix injectors are a sort of indirect injection in which the fuel is pumped into a sub-chamber to be swirled with compressed air before being sprayed into the combustion chamber area [1]. Many studies have suggested factors that influence the combustion and emissions of the burner.…”
Section: Introductionmentioning
confidence: 99%